Manajemen Talenta Pendidik dalam Menghadapi Transformasi Digital Pendidikan Islam: Strategi Penguatan Kompetensi dan Kinerja Profesional (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
Digital transformation has reshaped the competency requirements of educators in Islamic education, necessitating strategic human resource management capable of optimizing educators’ potential in a sustainable manner. This study aims to analyze the role of educator talent management in addressing digital transformation and to formulate strategies for strengthening educators’ professional competence and performance within the context of Islamic education. This study employs a qualitative approach using a literature review method. Data were obtained from relevant journal articles, academic books, and scholarly sources and were analyzed through systematic source selection, categorization, thematic analysis, and conceptual synthesis. The findings indicate that talent management plays a strategic role in identifying educators’ potential, developing competencies aligned with digital demands, empowering professional capacities, and sustaining performance. Competency development should not be limited to technological proficiency but should integrate pedagogical, professional, reflective, and ethical capabilities to ensure the substantive use of technology in educational practices. The findings further demonstrate that the effectiveness of talent development is influenced by leadership support, organizational culture, continuous professional learning, and developmental performance evaluation systems. Within Islamic education, these processes must remain grounded in Islamic values to ensure that digital transformation does not undermine the educational orientation toward character formation and learner integrity. Therefore, talent management can serve as an institutional strategy for developing adaptive, competent, innovative, and professional educators capable of responding to the dynamics of digital transformation in Islamic education. Keywords: talent management; digital transformation; educator competence; professional performance; Islamic education.